Analysis of risk factors in angiographically proven coronary artery disease in rural and urban Indian population. Prospective observational multicentre study: Kashmir Heart Survey - Jan Mohd Sheikh; Mohd Iqbal Dar; Hilal Ahmed Rather; Imran Hafeez; Aijaz Ahmed Lone; Aamir Rashid; Syed Bilal (Journal of Family Medicine and Primary Care)
Background: The global burden of cardiovascular diseases is increasing rapidly, and changing trends in epidemiological risk factors are identified among diverse Indian population. There has been a significant increase in heart attack deaths over the past 3 years after the COVID-19 pandemic. Are we missing a link? There is an urgent need for studies to confirm any epidemiological shift in coronary artery disease (CAD) risk factors. Aims and Objectives: To analyse the risk factors in patients with established CAD in rural and urban Indian Kashmiri populations in the post-COVID period. Material and Methods: A prospective observational study of all patients with angiographically proven CAD who have undergone revascularisation or have a clinical suspicion of CAD on the basis of symptoms or positive stress test and later proven to have CAD on coronary angiograms, coming from rural and urban areas of Jammu and Kashmir were enrolled for the study and screened for various modifiable and non-modifiable CAD risk factors. Data was compiled and analysed to know the pattern of various CAD risk factors in our population. Results: The study included total 600 patients (rural and urban 300 each), mean age was 59.13 ± 11.62 years. Male patients were 65.50% with a mean age of 57.53 ± 14.17 years and female patients were 34.50% with a mean age of 62.16 ± 10.02 years. In rural subgroup of 300 patients mean age was 60.99 ± 16.86 years and in the urban population we found a mean age of 57.26 ± 16.21 years. The most common risk factor was smoking in 76% rural and 67% urban. Diabetes (39% rural, 43% urban), dyslipidaemia (47.33%, 48.66% urban), hypertension (61% rural, 66% urban), obesity (23% rural, 29.33% urban) and physical inactivity (33.66% rural, 37.33% urban. Conclusion: CAD manifests earlier in males and urban populations. Smoking is the most common risk factor for CAD in the Kashmiri Indian population and is more common in the rural population. Coronary artery disease risk factors, such as physical inactivity, diabetes, smoking, hypertension, obesity and dyslipidaemia, are more common in the urban population. Preventive strategies should focus on modifying the risk factors to decrease the prevalence of CAD in communities.